Peran divisi internal control pada lembaga keuangan mikro syariah - Kholilah Kholilah; Kurniawati Meylianingrum; Mega Noerman Ningtyas; Tiara Juliana Jaya; Lutfi Ardhani (Jurnal Akuntansi Aktual, 2020)
This research is based on the rapid development of Sharia microfinance institutions that are not balanced with the professionalism of its management. The purpose of this research is to dig deeper into internal control conditions on Sharia microfinance institutions, to achieve these goals of research using qualitative methods with case study approaches. The data collection process is conducted through interviews, internal control report data collection, and FGD. The informant is the division of internal control and Operations manager at BMT X. The results showed that there are two business risks of Sharia microfinance institutions that are internal risks and external risks. The internal risks faced by Sharia microfinance institutions are human resources, institutional, and systems. External risks originating from outside the conditions of the Sharia microfinance institutions are financial technology developments and the level of outcomes that affect the capital of sharia financial institutions. Both of these risks can be minimized by optimizing internal control so that the trust to sharia microfinance institutions increases. The increased trust of stakeholders was able to restore the role of Sharia microfinance institutions as the spearhead of the lower-class community economy.